A Personal Introduction to Rethinking Problem-based Learning for the Digital Age (Savin-Baden and Fraser, 2024) - Maggi Savin-Baden (Journal of Problem Based Learning in Higher Education)
This reflection provides an introduction to, and reflection on, the new text Rethinking Problem-based Learning for the Digital Age (Savin-Baden and Fraser, 2024). It begins by telling the story and rationale for the creation of the book and then provides an overview of the text of the whole. The next section discusses the purpose of the book, and the final section analyses the importance of the notion of the postdigital for PBLonline. It argues that the postdigital as a concept and an approach is important in PBLonline because it prompts a rethinking of learning and the impact of neoliberalism of the university worldwide.